Proyecto de implementación y operatividad del "Centro de Rehabilitación Infantil TELETON", CRIT Michoacán - López Guillén, Fernando (Universidad Michoacana de San Nicolás de Hidalgo, 2014)
In the present thesis demonstrates the need to undertake new projects that meet the needs of the population, the importance of care and support people with disabilities in their process of rehabilitation. In Mexico there are 4'527, 784 inhabitants who have a disability that prevents him from performing their activities daily and in Michoacán have 212,874 disabled inhabitants, of whom 25,316 are children and adolescents from 0 to 18 years of age, according to the Census of population and housing 2010 from INEGI. There are civil associations nonprofit supporting this process, as the, "Foundation Telethon Mexico A.C." who built in Michoacán the CRIT number twenty-one in 2013 "Center of rehabilitation children Telethon", in the capital city of the State. The process of implementation, authorization, construction and start of operation, required three stages of efforts, 22 steps or governmental administrative procedures, 14 studies and technical projects, and a period of 1 year and a half of time (starting from August 15, 2012 and ending on February 20, 2014), to obtain the final operating license. Which means all methodology, procedures to follow, shown on the results obtained and given recommendations, which can serve as a guide for future similar projects, allowing you to optimize and streamline times of administrative formalities in their processes of implementation of new projects that detonate the economy, direct benefits, sources of employment for the entity, and to become a better quality and standard of living of our society.

En la presente Tesis se muestra la necesidad de emprender nuevos proyectos que satisfagan las necesidades de la población, la importancia de atender y apoyar a las personas con discapacidad en su proceso de rehabilitación. En México se tienen 4’527,784 habitantes que presentan alguna discapacidad que le impide realizar sus actividades cotidianas y en Michoacán se tienen 212,874 Habitantes discapacitados, de los cuales 25,316 son niños y adolescentes de 0 a 18años de edad, de acuerdo al Censo de Población y Vivienda 2010 del INEGI. Existen asociaciones civiles sin fines de lucro que apoyan éste proceso, como la, “Fundación Teletón México A.C.” quien en 2013 Construyó en Michoacán el CRIT numero veintiuno “Centro de Rehabilitación Infantil Teletón”, en la ciudad capital del estado. Su proceso de implementación, autorización, construcción e inicio de operación, requirió de tres etapas de gestiones, 22 pasos y/o trámites administrativos gubernamentales, 14 Estudios y/o proyectos técnicos, y un lapso de 1 año y medio de tiempo (Iniciando desde el 15 de Agosto de 2012 y concluyendo el 20 de Febrero de 2014), para obtener la licencia de funcionamiento final. Lo que implica toda una metodología, trámites a seguir, mostrados en los resultados obtenidos y de las recomendaciones dadas, que pueden servir de guía para proyectos futuros análogos, permitiendo optimizar y eficientar los tiempos de las gestiones administrativas en sus procesos de implementación de nuevos proyectos que detonen la economía, beneficios directos, fuentes de empleo para la entidad, y se conviertan en una mejor calidad y nivel de vida de nuestra sociedad.
Facultad de Contaduría y Ciencias Administrativas. Maestría en Administración
Keywords: info:eu-repo/classification/cti/5; FCCA-M-2014-1754; Planeación; Estrategia; Discapacidad; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/6046